Solve for y m(3-x)=2-y

Math
m(3-x)=2-y
Rewrite the equation as 2-y=m(3-x).
2-y=m(3-x)
Simplify m(3-x).
Tap for more steps…
Apply the distributive property.
2-y=m⋅3+m(-x)
Reorder.
Tap for more steps…
Move 3 to the left of m.
2-y=3⋅m+m(-x)
Rewrite using the commutative property of multiplication.
2-y=3m-mx
2-y=3m-mx
2-y=3m-mx
Subtract 2 from both sides of the equation.
-y=3m-mx-2
Multiply each term in -y=3m-mx-2 by -1
Tap for more steps…
Multiply each term in -y=3m-mx-2 by -1.
(-y)⋅-1=3m⋅-1+(-mx)⋅-1+(-2)⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=3m⋅-1+(-mx)⋅-1+(-2)⋅-1
Multiply y by 1.
y=3m⋅-1+(-mx)⋅-1+(-2)⋅-1
y=3m⋅-1+(-mx)⋅-1+(-2)⋅-1
Simplify each term.
Tap for more steps…
Multiply -1 by 3.
y=-3m+(-mx)⋅-1+(-2)⋅-1
Multiply (-mx)⋅-1.
Tap for more steps…
Multiply -1 by -1.
y=-3m+1mx+(-2)⋅-1
Multiply m by 1.
y=-3m+mx+(-2)⋅-1
y=-3m+mx+(-2)⋅-1
Multiply -2 by -1.
y=-3m+mx+2
y=-3m+mx+2
y=-3m+mx+2
Solve for y m(3-x)=2-y

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top